Evaluation of the determinants of uptake of oral rehydration salts with zinc in the management of childhood diarrhea in Kakamega County - Muhande, Irene K.; Mapesa, Job; Ouna, Benard (International Journal Of Community Medicine And Public Health, 2024)
Background: Diarrhea remains a significant public health concern, contributing to high child mortality, particularly in Sub-Saharan Africa and South Asia. Approximately 1.5 million cases of childhood diarrhea are reported annually in Kenya, with a prevalence of 16%. Despite the availability of affordable interventions like oral rehydration salts (ORS) and zinc supplementation, their utilization remains suboptimal in Kakamega County, where child mortality is 45 per 1,000. The combined impact of ORS and zinc in reducing childhood diarrhea and its consequences has not been adequately studied in Kakamega County. This study aims to assess the utilization of ORS and zinc in diarrhea management in Kakamega County. Methods: We utilized a cross-sectional design to evaluate current practices and outcomes in managing diarrhea among children under five years old. A random sampling approach was applied to ensure a representative sample. Key variables assessed included the frequency of diarrhea episodes, the use of ORS and zinc, and nutritional status. Statistical analyses, including Chi-square tests and descriptive methods, were used to examine the relationships between the variables in SPSS version 26. Results: Of the 246 children surveyed, 47.4% were under 10 months old. The study found that 26.8% of children had not received rotavirus vaccinations, and diarrhea was significantly (p<0.05) associated with poor nutritional outcomes. ORS had strong support (69.4%), but zinc supplementation showed moderate support (54.3%). Conclusions: The study highlights the need for increased uptake of ORS and zinc supplementation, as well as enhanced vaccination coverage to prevent diarrhea-related deaths and malnutrition in Kakamega County.